Neuro‐ and hepatic toxicological profile of (S)‐2, 4‐diaminobutanoic acid in embryonic, adolescent and adult zebrafish. Issue 11 (6th August 2019) - Ferraiuolo, Rosa‐Maria; Meister, Daniel; Leckie, Dominique; Dashti, Mohadeseh; Franke, Jonathan; Porter, Lisa A.; Trant, John F.
Abstract: ( S )‐2, 4‐Diaminobutanoic acid (DABA) is a noncanonical amino acid often co‐produced by cyanobacteria along with β‐ N ‐methylamino‐l ‐alanine (BMAA) in algal blooms. Although BMAA is a well‐established neurotoxin, the toxicity of DABA remains unclear. As part of our development of biocompatible materials, we wish to make use of DABA as both a building block and as the end‐product of enzymatically induced depolymerization; however, if it is toxic at very low concentrations, this would not be possible. We examined the toxicity of DABA using both in vivo embryonic and adult zebrafish models. At higher sublethal concentrations (700 μm ), the fish demonstrated early signs of cardiotoxicity. Adolescent zebrafish were able to tolerate a higher concentration. Post‐mortem histological analysis of juvenile zebrafish showed no liver or brain abnormalities associated with hepato‐ or neurotoxicity. Combined, these results show that DABA exhibits no overt toxicity at concentrations (100‐300 μm ) within an order of magnitude of those envisioned for its application. This study further highlights the low cost and ease of using zebrafish as an early‐stage toxicological screening tool. Abstract : Zebrafish are used to evaluate the toxicity of ( S )‐2, 4‐diaminobutanoic acid (DABA), a material useful for next‐generation drug delivery nanoparticles. DABA is produced by cyanobacteria and is toxic at high doses, but no studies have looked at sub‐millimolar concentrations. Below 300 μm, we observe no adverse effects in embryonic, adolescent or adult zebrafish. This is more than an order of magnitude above the envisioned operation concentration (20 μm ). Zebrafish are a useful tool for early toxicity screening.